2023
DOI: 10.3390/biomedicines11061598
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial DNA Transcription by POLRMT Inhibition or Depletion as a Potential Strategy for Cancer Treatment

Abstract: Transcription of the mitochondrial genome is essential for the maintenance of oxidative phosphorylation (OXPHOS) and other functions directly related to this unique genome. Considerable evidence suggests that mitochondrial transcription is dysregulated in cancer and cancer metastasis and contributes significantly to cancer cell metabolism. Recently, inhibitors of the mitochondrial DNA-dependent RNA polymerase (POLRMT) were identified as potentially attractive new anti-cancer compounds. These molecules (IMT1, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(282 reference statements)
1
0
0
Order By: Relevance
“…They found that MtPTAC effectively promotes the degradation of POLRMT mediated by ClpP in mitochondria and demonstrates its promising anti-tumor activity in vitro and in vivo [ 86 ]. This study confirms the findings proposed by Daglish et al [ 87 ]. Additionally, knockdown the POLRMT expression in vitro and in vivo also effectively inhibits tumor cell proliferation and migration [ 9 , 10 , 40 , 41 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...supporting
confidence: 94%
“…They found that MtPTAC effectively promotes the degradation of POLRMT mediated by ClpP in mitochondria and demonstrates its promising anti-tumor activity in vitro and in vivo [ 86 ]. This study confirms the findings proposed by Daglish et al [ 87 ]. Additionally, knockdown the POLRMT expression in vitro and in vivo also effectively inhibits tumor cell proliferation and migration [ 9 , 10 , 40 , 41 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...supporting
confidence: 94%